Self-directed learning and learning styles in medical residents.: Aprendizaje autodirigido y estilo de aprendizaje - Barragán Flores, Sofía Sarahí; León Vázquez, María de la Luz; Seefoó Jarquin, Patricia; Durán Barranco , Diana Isabel (Spanish Journal of Medical Education, 2026)
Introduction: Self-directed learning has become an essential skill for physicians in a context characterized by high workloads and access to vast amounts of information. Identifying learning styles can facilitate the use of strategies that promote autonomous learning. Objective: To determine if there is a relationship between self-directed learning and learning styles in resident physicians. Method: Observational and descriptive study; resident physicians assigned to the General Hospital of Family Medicine Subzone No. 8 were included. Data collected included age, sex, marital status, whether they had children, and place of origin. To assess self-directed learning, the Self-Directed Learning Readiness Scale was used, and the Honey-Alonso test was used to identify learning styles. Descriptive analysis and the Kruskal-Wallis test were used, considering a p-value less than 0.05 to be statistically significant. Results: Thirty-two physicians were included, 68.8% of whom were women; 22 were family medicine residents and 10 were epidemiologists. Reflective learning predominated at 31%. No statistically significant difference was observed between self-directed learning and learning styles in learning planning (p = 0.824), self-confidence (p = 0.708), self-management (p = 0.103), self-evaluation (p = 0.141), and desire to learn (p = 0.349). Discussion: Although it might be expected that resident physicians would have a high level of self-directed learning, less than 20% possess good skills in this area, which is unrelated to learning style. It has been suggested that there is a difference in learning style between men and women, with a predominance of theoretical and pragmatic styles, respectively. In the present study, the predominant learning style was reflective, with no differences between sexes, courses, or specialties. Conclusions: Specialty does not influence the preference for a learning style. The relationship between self-directed learning and learning styles is not statistically significant.